Ilhas, parentesco e mobilidade infantil: Diálogos Brasil-Cabo Verde (passando pela França) - Fernanda Bittencourt Ribeiro (Ciências Sociais Unisinos)
In this article I focus on comments raised by the presentation of Andréa Lobo in the Cycle of debates: Diálogos Brasil-Cabo Verde (Dialogues Brazil-Cape Verde). From an ethnographic study made at an institution of child protection, located on Yeu island (France), it offers some counterpoints between these two ethnographic contexts, on the Boa Vista and Yeu islands. Therefore, insularity, child mobility and rights of the child are issues addressed at the intersection of studies on kinship and anthropology of childhood. This exercise highlights the relative social isolation that brings families called "single-parent in difficulty" to the institution on Yeu island, in contrast to the abundance of relationships in which child mobility is central to the dynamics of kinship and relatedness on Boa Vista island.